Road marking paint composition with improved light reflection and reflection efficiency during rain
Patent Information
- Application Number
- KR1020260156608
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2026-03-04
- Filing Date
- 2026-08-20
- Publication Date
- 2026-09-09
Smart Images

Figure PAT00001 
Figure PAT00002 
Figure PAT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a paint composition for road markings with improved visibility in rainy conditions and a method for manufacturing the same. Specifically, the invention relates to a paint composition based on a composite functional capsule that can maximize light extraction and reflection efficiency by converting the shape of the water film on the road surface into a micro-lens array upon contact with moisture, and can ensure the durability of the pigment in a wet environment. Background Technology
[0003] In modern transportation systems, road markings are the most fundamental safety devices that assist drivers in lane compliance and identifying their driving routes. Particularly during nighttime driving, the visibility of road markings is a critical factor directly linked to traffic accident rates; to address this, retro-reflection technology, which incorporates high-refractive index glass beads into the paint to reflect headlights back to the driver, has been widely used. However, while this conventional method demonstrates excellent performance in dry conditions, it almost completely loses its effectiveness the moment a water film forms on the road surface during rainfall.
[0004] The most serious problem that occurs during rainy weather is the so-called "stealth lane" phenomenon. When the road surface gets wet, the exposed surface of the glass beads becomes submerged in a film of water. At this time, the difference in refractive index between the glass beads and the external medium (water) decreases rapidly, preventing the headlights from retroreflecting and causing them to scatter forward along the water surface or disappear through total internal reflection. As a result, drivers face a dangerous situation where they cannot identify the lane, which becomes a decisive cause of major accidents during rainy nights.
[0005] In addition, there have been attempts to introduce aluminate-based luminescent pigments with phosphorescent properties to improve visibility, but this also has fatal technical limitations. Aluminate-based pigments are chemically extremely vulnerable to moisture, so hydrolysis occurs immediately on the pigment surface when exposed to wet, rainy environments. If the crystal structure of the pigment is destroyed during this process, the luminescence performance deteriorates rapidly, which not only shortens the duration of the luminescence but also weakens the bonding strength of the paint itself, causing problems that accelerate peeling and wear of the road marking material.
[0006] Conventional high-brightness coating technologies have primarily focused on passive protection methods, such as increasing the refractive index of glass beads or the thickness of the coating film. However, these methods fail to fundamentally control changes in optical properties that occur during water film formation, and they do not overcome the limitations of durability, where visibility rapidly deteriorates as the surface structure wears down due to vehicle friction over time. In particular, engineering approaches that recognize the water film as an optical medium and actively utilize it are currently lacking.
[0007] Accordingly, the inventors have organically combined encapsulation technology, which ensures durability by physically isolating pigments from moisture, with pattern formation technology, which converts the water film formed on the road surface itself into a micro-lens array that focuses incident light. Through this, they aim to dramatically improve driving safety during nighttime rain by establishing an innovative optical system in which brightness actually increases as it gets wet. The problem to be solved
[0009] The problem that the present invention aims to solve is as follows.
[0010] First, the invention provides a composite functional capsule particle that protects the pigment from moisture and maximizes the extraction efficiency of internal luminescence through a glassy shell structure containing an aluminate-based luminescent pigment core and fine reflective particles.
[0011] Second, the goal is to construct an optical system that enhances light reflection and luminescence efficiency during rainfall by precisely controlling the water film into a spherical micro-lens shape upon hydration using a pattern-forming agent containing a hydrophilic film-forming agent and a hydrophobic domain-forming agent.
[0012] Third, by controlling the difference in refractive index between the glassy shell and the reflective particles, as well as the weight ratio between the components, to a critical range, it is possible to realize optical inversion luminance characteristics in which reflectance and luminance increase dramatically in the underwater state compared to the dry state. means of solving the problem
[0014] One aspect provides a paint composition for road marking comprising: a core comprising an aluminate-based phosphorescent pigment (phosphorescent pigment) and a glassy shell formed on the surface of the core and containing fine reflective particles; a thermoplastic resin binder in which the composite functional capsule particles are dispersed; and a pattern-forming agent dispersed within the thermoplastic resin binder, wherein the pattern-forming agent comprises a hydrophilic film-forming agent.
[0015] A paint composition for road marking according to one aspect may be characterized by having an optical inversion luminance characteristic, and the “optical inversion luminance characteristic” may refer to the unique optical behavior of the present invention in which visibility is improved during rain when a water film is formed compared to when dry.
[0016] Specifically, a paint composition for road marking according to one aspect exhibits a spectral reflectance in the 450 to 520 nm wavelength band that increases by more than 30% compared to the dry state in a water film-forming environment, and an underwater luminance of 100 cd / m² 2 It is characterized by maintaining the above.
[0017] The above “aluminate-based luminescent pigment” may refer to a component that absorbs an external energy source and emits light on its own during a blackout. In particular, in the case of the present invention, the chemical structure of the pigment, which is vulnerable to moisture, is protected through a modified coating layer formed on the surface of the base pigment, thereby preventing a decrease in luminescence efficiency due to hydrolysis during rain.
[0018] Specifically, the aluminate-based luminescent pigment is SrAl2O4:Eu 2+ , Dy 3+ ; CaAl2O4:Eu 2+ , Nd 3+ ; and BaAl2O4:Eu 2+ , Tm 3+ It may be characterized as a composite particle form comprising one or more base pigments selected from the group consisting of, and a modified coating layer formed on the surface of the base pigment and comprising one or more of ZrO2, SiO2, and Al2O3.
[0019] In one experimental example, a modified coating layer having a thickness of 50 to 100 nm comprising ZrO2 and Al2O3 was formed on the surface of SrAl2O4:Eu 2+ , Dy 3+ By applying a luminous pigment core, the hydrolysis reaction on the pigment surface is effectively blocked even in high-temperature and high-humidity rainy environments, thereby suppressing the premature degradation of luminescence performance.
[0020] The above “fine reflective particles” may be dispersed within a glassy shell and act as scatterers that help extract internal light, while simultaneously serving to strongly retroreflect external incident light.
[0021] Specifically, the fine reflective particles may comprise one or more selected from the group consisting of glass particles containing SiO2 or TiO2; ceramic beads; aluminum silicate; barium titanate and magnesium oxide (MgO), and specifically may be barium titanate (BaTiO3), but are not particularly limited thereto.
[0022] The above “complex functional capsule particles” are a multi-structure comprising a core containing an aluminate-based luminescent pigment and a glassy shell formed on the surface of the core containing fine reflective particles, wherein the physical specifications of the complex functional capsule particles can serve as a key factor in determining the durability of the coating film and the optical extraction efficiency.
[0023] Specifically, the composite functional capsule particles have a ratio of the thickness of the glassy shell to the diameter of the core of 1:0.05 to 1:0.2; a packing rate of the fine reflective particles within the glassy shell of 5 to 20 vol%; and an average particle size (D) of 20 to 100 μm. 50 It may be characterized by having ).
[0024] If the above thickness ratio is less than 1:0.05, the formation of the glassy protective film is incomplete, and as moisture penetrates into the pigment core in a humid environment, hydrolysis is accelerated and the duration of light retention may be drastically shortened. Conversely, if the above thickness ratio exceeds 1:0.2, the transmission path of light emitted from the inside becomes longer due to the excessive shell thickness, and optical interference and scattering losses occur, which may significantly reduce the luminance in water.
[0025] In one experimental example, in embodiments satisfying a ratio of shell thickness to core diameter of 1:0.05 to 1:0.20, the underwater luminance is 100 cd / m 2Excellent optical inversion luminance characteristics with an abnormality and reflectance increment of more than 30% were observed, and it was confirmed that it exhibits excellent visibility.
[0026] In addition, if the above-mentioned packing rate is less than 5 vol%, there may be a lack of scattering centers within the shell, resulting in insignificant light extraction efficiency; conversely, if the above-mentioned packing rate exceeds 20 vol%, the transparency of the glassy shell may decrease due to excessive particle density, and the transmission path of internal light may be physically blocked, causing a rapid drop in underwater brightness.
[0027] In addition, if the above average particle size is less than 20 μm, the scattering area of individual particles is insufficient, which may reduce visibility, and conversely, if it exceeds 100 μm, the bonding area with the coating film decreases relatively compared to the volume of the particles, so the particles may easily detach upon external friction, causing a sharp drop in brightness retention rate.
[0028] In one experimental example, in an example satisfying a concentration (filling rate) of fine reflective particles embedded inside a glassy shell of 5 to 20 vol%, the underwater luminance is 100 cd / m² 2 Excellent reflectivity performance exceeding was observed, and when the average particle size of the composite functional capsule particles is in the range of 20 to 100 µm, 100 cd / m² 2 It was confirmed that it exhibits the above underwater luminance and good adhesion.
[0029] In addition, the difference in refractive index (Δn) between the glassy shell and the fine reflective particles may be 0.20 to 0.50.
[0030] If the above refractive index difference is less than 0.20, the optical interface between the media is not clearly formed, so the scattering effect may be minimal, and conversely, if it exceeds 0.50, as the angle of refraction at the particle interface deviates from the critical angle, a significant amount of light is totally reflected internally and extinguished, resulting in light loss and degrading performance.
[0031] In one experimental example, when the difference in refractive index was in the range of 0.20 to 0.50, underwater visibility increased dramatically through a strong scattering effect without total reflection loss, and in particular, critical significance was confirmed in which the increment of underwater luminance and reflectance reached a peak when Δn was 0.35.
[0032] The above “thermoplastic resin binder” refers to a polymer matrix that firmly fixes the composite functional capsule particles and pattern-forming agent of the present invention to the road surface and forms the physical framework of the coating film. It provides workability by ensuring fluidity through high-temperature heating during construction, and after cooling, forms strong adhesion to the asphalt or concrete substrate, thereby playing a role in maintaining the structural stability of the coating film even under mechanical friction caused by vehicle loads or harsh weather changes.
[0033] In particular, the binder according to the present invention must have excellent light transmittance so that light transmitted through the glassy shell can be extracted and retroreflected without loss by having a transparent nature, and can act as a dispersion medium that helps the hydrophilic film agent and the hydrophobic domain forming agent form an appropriate phase separation structure.
[0034] The above thermoplastic resin binder may be one or more selected from the group consisting of acrylic resin, silicone resin, polyester resin, hydrocarbon-based petroleum resin and their modifications or copolymers, and specifically, it may be an acrylic-silicone graft copolymer considering the adhesion performance with the road surface and the efficiency of controlling phase separation of the pattern-forming agent, but is not particularly limited thereto.
[0035] The above “pattern forming agent” may refer to a component that actively controls the geometric shape of a water film by locally changing the surface energy of the road surface water film upon contact with moisture, and may include a hydrophilic film-forming agent and / or a hydrophobic domain-forming agent.
[0036] The above-mentioned hydrophilic film agent refers to a component that induces the rapid and uniform formation of a water film on the surface of a road marking based on its affinity for water. It serves as a substrate that wets the entire road surface with water during rainfall to secure a light transmission path, and can function as a dispersion medium that physically constrains the shape of the water film by interacting with the hydrophobic domain forming agent described later.
[0037] Specifically, the hydrophilic coating agent may comprise one or more selected from the group consisting of polyether-modified siloxane, fluorinated nonionic surfactants, polyethylene glycol (PEG) dispersions, and hydrophilic acrylic resins, and specifically may be polyether-modified siloxane, but is not particularly limited thereto. In the case of polyether-modified siloxane, by forming a thin, transparent water film on the surface of the coating film through low surface tension, it can provide an optical window through which light extracted from the internal composite functional capsule can be emitted to the outside without scattering loss.
[0038] In addition, the pattern forming agent may be characterized by further including a hydrophobic domain forming agent.
[0039] The above-mentioned hydrophobic domain-forming agent may refer to a component that forms localized hydrophobic regions within the continuous water film formed by the above-mentioned hydrophilic film-forming agent, thereby intentionally disrupting the continuity of the water film or changing its curvature. This can act as a key control factor that transforms the water film from a simply planar film into an independent spherical micro-lens array structure.
[0040] Specifically, the hydrophobic domain forming agent may include one or more selected from the group consisting of POSS (Polyhedral Oligomeric Silsesquioxane), fluoroalkyl silane, silicone-modified wax, and PTFE (Polytetrafluoroethylene) micropowder, and specifically may be POSS, but is not particularly limited thereto.
[0041] In one experimental example, it was confirmed that when POSS, a nanostructured organic-inorganic hybrid material, is applied, the three-dimensional cage structure of POSS forms a micro-lens shape with maximized light-gathering efficiency by precisely confining the curvature of the water film between the hydrophilic films.
[0042] In addition, the hydrophilic coating agent and the hydrophobic domain forming agent may be characterized by being included in a weight ratio of 10:1 to 5:1.
[0043] If the above weight ratio exceeds 10:1, the dominance of the hydrophilic component is excessive, and the force binding the water film to individual lenses is insufficient, so the improvement in visibility may be minimal; conversely, if the above weight ratio is less than 5:1, the continuity of the water film is completely destroyed due to excessive water repellency, physically blocking the light transmission path, which may result in a problem where the brightness decreases drastically.
[0044] In one experimental example, it was confirmed that when the weight ratio of a hydrophilic coating agent to a hydrophobic domain forming agent satisfies the range of 10:1 to 5:1, the underwater luminance is maintained at 100 cd / m² or higher and the spectral reflectance increases dramatically by more than 30% compared to the dry state, exhibiting optical inversion luminance characteristics. In particular, under the condition where the weight ratio is 7.5:1, the underwater luminance was recorded at 148.2 cd / m² and the reflectance increment at 82.4%, confirming that the light-gathering synergy caused by the formation of spherical microlenses is maximized.
[0046] Another aspect is to provide a road marking material comprising the above-mentioned paint composition for road marking.
[0047] Specifically, the road marking material may be any one selected from the group consisting of liquid paint for road marking, tape for road marking, sheet for road marking, spray for road marking repair, and traffic safety block; specifically, it may be liquid paint for road marking, but is not particularly limited thereto.
[0048] The aforementioned “road marking material” encompasses all forms of visual guides installed on a road surface to promote road traffic safety and smooth flow, and may refer to a physical entity formed by applying, attaching, or embedding the paint composition according to the present invention. The road marking material of the present invention efficiently retroreflects incident light during nighttime rain and ensures visibility through self-luminescence, thereby assisting drivers in adhering to their lanes and preventing traffic accidents even under harsh weather conditions.
[0049] For example, the liquid paint may include both room-temperature application type and heat-fusion type formulations, and the tape and sheet types are advantageous for maintaining high brightness performance for a long period of time by transferring a uniform coating structure, pre-manufactured in a factory, onto the road surface. In addition, the repair spray is suitable for restoring optical performance by locally reapplying worn areas of existing lanes, and the traffic safety block can be installed on speed bumps or median barriers to provide three-dimensional visibility.
[0050] A road marking material according to one aspect may further include various auxiliary components known in the art to reinforce the physical properties of the paint or improve workability, in addition to the composition of the present invention.
[0051] Specifically, the above auxiliary components may include titanium dioxide (White) or lead-free yellow pigment (Yellow) as coloring pigments to ensure daytime visibility, and may use calcium carbonate, silica sand, or silica powder appropriately blended as fillers to increase the mechanical strength and slip resistance of the coating film. In addition, plasticizers to impart flexibility to the coating film to prevent cracking during winter, dispersants and anti-settling agents to maintain a uniform dispersion state of the composite functional capsules within the composition and prevent sedimentation during storage, and UV stabilizers and antioxidants to prevent yellowing or aging of the binder due to prolonged exposure to ultraviolet rays may be organically combined within the scope of implementing the technical concept of the present invention, but are not particularly limited thereto.
[0053] Another aspect provides a method for manufacturing a paint composition for road marking, comprising: (a) a step of preparing a dispersion by pre-mixing a hydrophobic domain-forming agent with a portion of a pattern-forming agent; (b) a step of adding a thermoplastic resin binder, a composite functional capsule particle, and the remainder of the pattern-forming agent to the dispersion; (c) a step of mixing each of the added components to form a structure in which a hydrophilic film agent and a hydrophobic domain-forming agent are dispersed within the binder; and (d) a step of homogenizing the mixture in which the dispersion structure is formed to formulate it into a paint composition.
[0054] In step (a) above, the preliminary mixing step is a pretreatment process to ensure that a small amount of hydrophobic domain-forming agent is uniformly distributed within the final paint without clumping.
[0055] Specifically, there is technical significance in ensuring content uniformity by first mixing a fine powder or highly concentrated hydrophobic component, such as POSS, with a portion of the hydrophilic coating agent, and then creating a dispersion environment that allows for rapid and even diffusion into the entire binder system during the mixing process.
[0056] In step (b) above, the input of each raw material can be performed through a manual input method or a quantitative supply system. At this time, by sequentially inputting composite functional capsule particles and a residual amount of pattern-forming agent using a transparent thermoplastic resin binder as a base, rapid aggregation between the components can be prevented and chemical affinity can be maximized.
[0057] In step (c) above, the “dispersion structure” or “phase separation structure” may refer to a state in which a hydrophilic coating agent and a hydrophobic domain-forming agent having different properties are physically isolated within a single medium, such as a transparent thermoplastic resin binder, to form independent regions of nano to micro scales.
[0058] This is an essential process for inducing the microlensification of the water film, which is the core mechanism of the present invention, and induces the two components to be uniformly cross-dispersed through physical shear force generated during the mixing process. The mixing can be performed using a high-speed mixer, etc., and specifically, it may involve forming a structure in which each active ingredient is optimally arranged between binder particles through high-speed stirring of 2,000 RPM or more.
[0059] In step (d) above, the “formulation” may refer to a process of finally adjusting the particle size of the mixture with the formed dispersion structure and imparting physical stability to complete it in a state suitable for actual road construction.
[0060] In this step, a porous structure is established by controlling the micropores within the composition using a homogenizer, thereby immediately forming a water film upon contact with moisture and converting it into a micro-lens shape. Through this formulation process, the paint of the present invention acquires final physical properties in which the preset optical inversion luminance characteristics can be precisely realized on the actual road surface after application. Effects of the invention
[0062] The road marking paint composition according to the present invention overcomes the physical limitations of conventional paints, which experience a sharp decline in visibility during rain, and provides an optical inversion luminance effect in which light reflection and luminescence efficiency are dramatically improved in a water film-forming environment.
[0063] In particular, by perfectly protecting the luminescent pigment from moisture through a composite functional capsule with a glassy shell structure containing fine reflective particles, it prevents the hydrolysis of the pigment and ensures long-term durability, while maximizing the extraction efficiency of internal luminescence through an optimized refractive index design.
[0064] In addition, a water film in the form of a micro-lens controlled by a pattern-forming agent can efficiently focus and retroreflect incident light, thereby clearly providing drivers with visual information during nighttime rain, which can drastically prevent road traffic accidents. Furthermore, through a highly durable capsule structure, it extends the maintenance cycle of the paint and maintains stable brightness even in harsh road conditions, thereby achieving excellent effects in simultaneously reducing social costs and improving traffic safety. Specific details for implementing the invention
[0066] The following examples will be explained in more detail. However, these examples are for illustrative purposes only and the scope of the present invention is not limited to these examples.
[0068] Preparation Example. Preparation of a paint composition for road markings
[0069] To manufacture a road marking paint composition with improved visibility in rainy conditions according to the present invention, the following process was performed.
[0070] First, to manufacture composite functional capsule particles, a hydrolysis reaction was induced by mixing TEOS (Tetraethyl orthosilicate), a silica (SiO2) precursor and the main component of the glassy shell, with water ammonia, a reaction catalyst, in an ethanol solvent. At this time, BaTiO3, a high-refractive index fine particle, was added to the shell-forming sol solution, and dispersion treatment was performed for 30 minutes using an ultrasonic disperser to induce the uniform inclusion of fine reflective particles within the glassy matrix. SrAl2O4:Eu, in which a modified coating layer with a thickness of 50 to 100 nm containing ZrO2 and Al2O3 was formed on the surface of the above reaction solution. 2+ , Dy 3+ A luminescent pigment core was introduced to form a glassy shell containing fine reflective particles on the core surface, and the resulting mixture was centrifuged and dried to obtain powdered composite functional capsule particles.
[0071] Next, a homogeneous dispersion was prepared by pre-mixing POSS (Polyhedral Oligomeric Silsesquioxane), a hydrophobic domain-forming agent, with a portion of polyether-modified siloxane, one of the pattern-forming agents, in a weight ratio of 1:1. An acrylic-silicone graft copolymer, which is a thermoplastic resin binder, the previously prepared composite functional capsule particles, and the remaining amount of pattern-forming agent were sequentially added to the dispersion, and the mixture was stirred for 30 minutes at a speed of 2,000 RPM using a high-speed mixer. Through this process, the hydrophilic coating agent and the hydrophobic domain-forming agent were physically isolated within the binder to induce the formation of a phase-separated structure at the nano to micro scale. Finally, the mixture was passed through a homogenizer to complete a porous paint composition capable of forming a micro-lens-shaped water film upon contact with moisture.
[0073] Experimental Example 1. Confirmation of structural and specification optimization characteristics of multi-functional capsule particles
[0074] To verify the critical significance of the physical specifications of the composite functional capsule particles according to the present invention on optical performance and durability, capsules and compositions were prepared using the same method and conditions as the above-mentioned preparation example, but examples and comparative examples were constructed with only specific variables differing according to the experimental purpose, and an analysis was performed.
[0075] For the experiment, a 15cm × 15cm aluminum panel was prepared by degreasing and washing it with ethanol for precise measurement, and after applying it to a uniform thickness of 2.0mm using an automatic applicator, it was manufactured by melt bonding at 200℃ and stabilizing drying for 24 hours.
[0077] 1-1. Verification of Characteristics of Complex Functional Capsule Particles According to the Ratio of Shell Thickness to Core Diameter
[0078] In order to confirm the characteristics according to the ratio of the thickness of the shell to the core constituting the composite functional capsule particles, examples and comparative examples with different shell thickness ratios were prepared by adjusting the input rate and reaction time of the TEOS precursor during the process of the above manufacturing example.
[0079] The thickness ratio was measured by observing the cross-section of each manufactured capsule particle using a field-effect scanning electron microscope (FE-SEM), and the paint composition specimens containing these particles were exposed to a rainfall simulator (20 mm / h) to measure the underwater luminance and spectral reflectance increments. A spectroradiometer (CS-2000) and a spectrophotometer equipped with an integrating sphere were used to evaluate optical properties. In addition, to evaluate long-term moisture resistance, each specimen was subjected to accelerated exposure for 1,000 hours in a constant temperature and humidity chamber under conditions of 85°C and 85% RH, and the light duration was measured as the time until the luminance decreased to 10% of the initial value in a dark state.
[0080] [Table 1]
[0081]
[0083] As a result, in embodiments where the shell thickness ratio satisfies the range of the present invention (1:0.05 to 1:0.20), the underwater luminance is 100 cd / m 2 Excellent optical inversion luminance characteristics with an anomalous and reflectance increment of more than 30% were observed, and notably, in Examples 1-2, an underwater luminance of 112.8 cd / m² was recorded. 2 It recorded and displayed the most outstanding visibility.
[0084] On the other hand, in Comparative Example 1-1, where the shell thickness ratio fell below the lower limit, the formation of the vitreous protective film was incomplete. As moisture penetrated to the core pigment in an accelerated humidity environment, the hydrolysis of the pigment was accelerated, resulting in a problem where the luminescence duration was drastically shortened to 2.5 hours. Conversely, in Comparative Example 1-2, where the shell thickness ratio exceeded the upper limit, although the physical protective function of the pigment was excellent, the excessive shell thickness lengthened the transmission path of internally emitted light, causing optical interference and scattering losses, resulting in an underwater luminance of 62.8 cd / m². 2 It was confirmed that a critical adverse effect of deterioration to [level] occurred.
[0085] From this, it was confirmed that the core:shell thickness ratio proposed in the present invention can secure durability by isolating pigments from moisture in an underwater environment, while simultaneously effectively extracting internal light to the outside, thereby dramatically improving driver visibility during nighttime rain.
[0087] 1-2. Confirmation of characteristics based on the packing ratio of fine reflective particles within the shell
[0088] We aimed to verify the effect of the concentration of micro-reflective particles embedded inside a glassy shell on the efficient extraction of internal light and the retroreflection performance of external incident light.
[0089] Specifically, BaTiO3, a high-refractive index fine particle, was added to a sol solution for shell formation, and dispersion treatment was performed for 30 minutes using an ultrasonic disperser to prepare examples and comparative examples with different particle packing ratios (vol%). For each prepared specimen, the underwater luminance, which represents the luminescence intensity of the internal pigment, and the reflection efficiency of external light were measured in a rainfall simulator (20 mm / h) environment to derive the optimal density of the scatterer.
[0090] [Table 2]
[0091]
[0093] As a result, in the case of embodiments where the filling rate satisfies the scope of the present invention, the underwater luminance is 100 cd / m 2 Excellent reflective performance exceeding [the value] was observed, and in particular, in Examples 1-5 with a fill rate of 12%, both underwater luminance and reflective efficiency reached their peak.
[0094] On the other hand, in Comparative Example 1-3, where the packing ratio fell below the lower limit, the light extraction efficiency was negligible due to a lack of scattering centers within the shell. Conversely, in Comparative Example 1-4, where the packing ratio exceeded the upper limit, the transparency of the glassy shell was reduced and the transmission path of internal light was blocked due to excessive particle density, resulting in an underwater luminance of 74.2 cd / m². 2 A critical adverse effect of falling to [amount] was confirmed.
[0095] From this, it has been proven that the reflective particles of appropriate density proposed in this invention perform a dual function of efficiently extracting internal filter light and strongly scattering external light.
[0097] 1-3. Confirmation of film stability according to the average particle size of composite functional capsule particles
[0098] We aimed to verify the effect of capsule particle size on the physical strength of the coating film and the optically effective area during rain.
[0099] Specifically, by controlling the size of the sprayed droplets by adjusting the spray pressure applied to the two-fluid nozzle of the spray dryer and the feed rate of the raw material slurry, the average particle size (D) of the finally obtained composite functional capsule particles is 50 Examples and comparative examples were prepared with different values. For each specimen, the underwater luminance was measured, and the luminance retention rate was analyzed after a cross-cut adhesion test and a Taber abrasion test according to ASTM D3359 standards to evaluate the actual lifespan and stability as a road marking material.
[0100] [Table 3]
[0101]
[0103] As a result, for the examples with an average particle size in the range of 20 to 100 μm, 100 cd / m 2 The brightness and good adhesion were confirmed, and in particular, the optimal balance was confirmed in Examples 1-8 with an average particle size of 60 μm.
[0104] On the other hand, Comparative Example 1-5, in which the particle size fell below the lower limit, had insufficient scattering area of individual particles, resulting in reduced visibility; conversely, Comparative Example 1-6, in which the particle size exceeded the upper limit, showed a limitation in which the particle easily detached upon external friction as the bonding area with the coating film decreased relative to the volume of the particle, causing the brightness retention rate to drop sharply to 54.3%.
[0105] From this, it was confirmed that the particle size range proposed in the present invention is a critical range for simultaneously securing the durability and nighttime visibility of the coating film.
[0107] Experimental Example 2. Confirmation of optical synergy based on the difference in refractive index between the glassy shell and micro-reflective particles
[0108] We intended to verify the effect of the difference in refractive index (Δn) between the glassy shell medium and the internal fine reflective particles according to the present invention on the improvement of Mie scattering intensity for light extraction and underwater visibility. To this end, specimens of the example and comparative example were prepared by maintaining the same specimen preparation method and analysis conditions as in the above preparation example and experimental example 1, while changing the composition ratio of the glassy shell to precisely control Δn.
[0109] Specifically, to verify the optical synergy based on the difference in refractive index (Δn) between the glassy shell medium and the internal fine reflective particles, the refractive index of the glassy shell was precisely controlled while the internal reflective particles were fixed as BaTiO3 (n = approximately 2.4). The control of the glassy shell's refractive index was performed by gradually varying the mixing ratio of the silica (SiO2) precursor and the titania (TiO2) precursor in the shell-forming sol solution from 8:2 to 3:7 by weight. Through this, specimens were prepared such that the difference in refractive index between the media was 0.20 (3:7, Example 2-1), 0.35 (5.5:4.5, Example 2-2), and 0.50 (8:2, Example 2-3), respectively. As comparative examples, analysis was performed including cases where the refractive indices of the shell and the particles were nearly identical (Δn = 0.05) and cases where the difference in refractive index was excessively high (Δn = 0.80).
[0110] The optical properties were evaluated in an environment where a water film was formed on the surface using a rainfall simulator. The reflectance increment and scattering index in the underwater state compared to the dry state were quantitatively analyzed using a spectrophotometer (UV-Vis-NIR) equipped with an integrating sphere, targeting the wavelength range of 450 to 520 nm, which is the main emission band of the luminescent pigment. In addition, the combined synergy of the retroreflection effect caused by incident light and the self-luminous efficiency caused by the internal pigment was verified by measuring the underwater luminance in a dark state using a spectroradiometer (CS-2000).
[0111] [Table 4]
[0112]
[0114] As a result, for embodiments where the difference in refractive index (Δn) satisfies the scope of the present invention, the underwater luminance is 100 cd / m 2 Excellent optical inversion luminance characteristics with an anomalous and reflectance increment of more than 30% were observed. In particular, in Example 2-2, an underwater luminance of 125.4 cd / m² was recorded. 2It showed the most significant optical synergy, recording a reflectance increment of 78.2%.
[0115] On the other hand, in Comparative Example 2-1, where the difference in refractive index fell below the lower limit, the optical interface between the shell medium and the internal particles was not clearly formed, resulting in a negligible Mie scattering effect, which led to a reflection increment of only 12.4% in water. Conversely, in Comparative Example 2-2, where the difference in refractive index exceeded the upper limit, it was confirmed that a critical adverse effect occurred in which performance was degraded due to light loss, where a significant amount of light was not extracted to the outside of the shell but was totally reflected and extinguished inside, as the angle of refraction at the particle interface deviated from the critical angle.
[0116] From this, it was confirmed that the refractive index range proposed in the present invention is a physical prerequisite for maximizing the extraction efficiency of internal luminescence while simultaneously strongly retroreflecting external incident light.
[0118] Experimental Example 3. Confirmation of critical significance according to component combination and weight ratio of pattern-forming agents
[0119] We intended to verify the microlensification of the water film, which is the core mechanism of the composition of the present invention, and the resulting optical inversion luminance effect. Specifically, while following the same specimen manufacturing process as in the above Preparation Example and Experimental Example 1, an experimental group was formed as follows to confirm the synergy according to the combination of components of the pattern-forming agent.
[0121] 3-1. Verification of Microlens Formation Efficiency and Synergy According to the Type of Hydrophobic Domain Forming Agent
[0122] Compositions were prepared by fixing a hydrophilic film agent with a polyether-modified siloxane and replacing it with POSS, a fluoroalkyl silane, and a silicone-modified wax, respectively, as hydrophobic domain-forming agents. As a control, a composition containing only a hydrophilic film agent without any hydrophobic components was used.
[0123] All specimens were exposed to a rainfall simulator (20 mm / h) to form a water film, and then the underwater luminance in a dark state was measured using a spectroradiometer (CS-2000). In addition, the structural form of the water film was analyzed by calculating the reflectance increment in the 450 to 520 nm wavelength band using a spectrophotometer equipped with an integrating sphere and quantifying the surface energy using a water contact angle meter.
[0124] [Table 5]
[0125]
[0127] As a result, in Example 3-1, which applied POSS, a nanostructured organic-inorganic hybrid material, the underwater luminance was 148.2 cd / m² 2 An overwhelmingly significant optical enhancement effect was observed, recording a reflectance increment of 82.4%.
[0128] On the other hand, when general fluorine-based or wax-based hydrophobic materials are used, the underwater luminance is 100 cd / m 2 It was confirmed that although it exceeded [the value], the synergy range compared to POSS was not significant. In particular, compared to the control group, Example 3-1 exhibited superhydrophobic properties with a contact angle of 110 degrees or more and was confirmed to convert the water film into independent spherical water droplet shapes.
[0129] From this, it was confirmed that the three-dimensional cage structure of POSS is most suitable for the purpose of the present invention and the problem to be solved by forming a micro-lens array with maximized light-gathering efficiency through physically and precisely constraining the curvature of the water film between the hydrophilic membranes of polyether-modified siloxane.
[0131] 3-2. Verification of properties according to the weight ratio between hydrophilic and hydrophobic pattern-forming agents
[0132] Based on the optimal combination (polyether-modified siloxane and POSS) identified in Experimental Example 3-1 above, the effect of changes in the weight ratio between the two components on the microlensification mechanism and optical critical performance of the water film was precisely analyzed.
[0133] For the experiment, aluminum panel specimens were prepared using the same method as in the above-mentioned Preparation Example and Experimental Example 1, but the weight ratio of the hydrophilic coating agent to the hydrophobic domain-forming agent was varied stepwise within the range of 15:1 to 2:1 to construct the examples and comparative examples. The optical measurement equipment and rainfall reproduction environment were maintained identically to those in Experimental Examples 2 and 3-1 to ensure the objectivity of the data. In particular, the correlation between changes in the morphological characteristics of the water film, such as the domain formation state and continuity maintenance of the water film according to changes in the weight ratio, and the resulting optical inversion luminance effect was precisely analyzed.
[0134] [Table 6]
[0135]
[0137] As a result, for embodiments satisfying a specific weight ratio range in the present invention, the underwater luminance is 100 cd / m 2 Excellent performance with an abnormality and reflectance increment of over 30% was confirmed, and in particular, in Examples 3-5, all indicators reached their peak and significant synergy was confirmed.
[0138] On the other hand, in the comparative example where the specific gravity of the hydrophobic domain-forming agent fell below the lower limit, the underwater luminance was 96.2 cd / m² due to the excessive dominance of the hydrophilic coating agent and the insufficient force to restrain the water film to individual lenses. 2 It remained at [value], whereas in the comparative example where an excessive amount of hydrophobic components was added, the excessive water repellency completely destroyed the continuity of the water film, resulting in a counterproductive effect of physically blocking the light transmission path, which caused the luminance to be 74.5 cd / m². 2 It showed results of decreasing to [amount].
[0139] From this, it was confirmed that the weight ratio between the hydrophilic coating agent and the hydrophobic domain forming agent proposed in the present invention is a technical critical range that can maximize the optical inversion luminance effect without disrupting the continuity of the water film by optimally controlling the microlensification mechanism of the water film.
[0141] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.
Claims
Claim 1 A paint composition for road marking comprising: a core containing an aluminate-based luminescent pigment and a vitreous shell formed on the surface of the core containing fine reflective particles; a thermoplastic resin binder in which the composite functional capsule particles are dispersed; and a pattern-forming agent dispersed within the thermoplastic resin binder, wherein the pattern-forming agent comprises a hydrophilic film-forming agent. Claim 2 A paint composition for road marking according to claim 1, characterized in that the pattern forming agent further comprises a hydrophobic domain forming agent. Claim 3 In claim 1, the aluminate-based luminescent pigment is SrAl2O4:Eu 2+ , Dy 3+ ; CaAl2O4:Eu 2+ , Nd 3+ ; and BaAl2O4:Eu 2+ , Tm 3+ A paint composition for road marking, characterized by being in the form of a composite particle comprising one or more base pigments selected from the group consisting of, and a modified coating layer formed on the surface of said base pigment and comprising one or more of ZrO2, SiO2, and Al2O3. Claim 4 A paint composition for road marking according to claim 1, wherein the fine reflective particles comprise one or more selected from the group consisting of glass particles containing SiO2 or TiO2; ceramic beads; aluminum silicate; barium titanate; and magnesium oxide (MgO). Claim 5 A paint composition for road marking according to claim 2, wherein the hydrophilic film agent comprises one or more selected from the group consisting of polyether-modified siloxane, fluorinated nonionic surfactant, polyethylene glycol (PEG) dispersion, and hydrophilic acrylic resin, and the hydrophobic domain forming agent comprises one or more selected from the group consisting of POSS (Polyhedral Oligomeric Silsesquioxane), fluoroalkyl silane, silicone-modified wax, and PTFE (Polytetrafluoroethylene) micropowder. Claim 6 In claim 1, the composite functional capsule particles have a ratio of the thickness of the glassy shell to the diameter of the core of 1:0.05 to 1:0.2; a filling rate of the fine reflective particles within the glassy shell of 5 to 20 vol%; and an average particle size (D) of 20 to 100 μm. 50 A paint composition for road markings characterized by having ). Claim 7 A paint composition for road marking according to claim 1, characterized in that the difference in refractive index (Δn) between the glassy shell and the fine reflective particles is 0.20 to 0.
50. Claim 8 A paint composition for road marking according to claim 2, characterized in that the hydrophilic film agent and the hydrophobic domain forming agent are included in a weight ratio of 10:1 to 5:
1. Claim 9 In claim 1, the composition exhibits a spectral reflectance in the 450 to 520 nm wavelength band that increases by at least 30% compared to the dry state in a water film forming environment, and an underwater luminance of 100 cd / m² 2 A paint composition for road markings characterized by having optical inversion luminance characteristics that are maintained above. Claim 10 A road marking material comprising a paint composition for road marking according to any one of claims 1 to 9, wherein the road marking material is any one selected from the group consisting of a liquid paint for road surface marking, a tape for road surface marking, a sheet for road surface marking, a spray for road marking repair, and a traffic safety block. Claim 11 A method for manufacturing a paint composition for road marking according to any one of claims 1 to 9, comprising: (a) a step of preparing a dispersion by pre-mixing a hydrophobic domain forming agent with a portion of a pattern forming agent; (b) a step of adding a thermoplastic resin binder, a composite functional capsule particle, and the remaining amount of a pattern forming agent to the dispersion; (c) a step of mixing each of the added components to form a structure in which a hydrophilic film agent and a hydrophobic domain forming agent are dispersed within the binder; and (d) a step of homogenizing the mixture in which the dispersion structure is formed to formulate it into a paint composition.
